2012
DOI: 10.1177/0300985812456213
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electron Microscopy to Classify Canine Perivascular Wall Tumors

Abstract: The histologic classification of canine perivascular wall tumors (PWTs) is controversial. Many PWTs are still classified as hemangiopericytomas (HEPs), and the distinction from peripheral nerve sheath tumors (PNSTs) is still under debate. A recent histologic classification of canine soft tissue sarcomas included most histologic types of PWT but omitted those that were termed undifferentiated. Twelve cases of undifferentiated canine PWTs were evaluated by transmission electron microscopy. The ultrastructural fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 30 publications
2
42
0
3
Order By: Relevance
“…According to recent studies a small subgroup of PWTs with equivocal morphology and lack of specifi c immunohistochemical markers may exist, so that in the case of extensive immunohistochemical negativity a defi nitive diagnosis may not be reached. In order to provide clarity, further IHC studies should be performed in the presence of a defi nitive diagnosis based on ultrastructural investigation [29].…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies a small subgroup of PWTs with equivocal morphology and lack of specifi c immunohistochemical markers may exist, so that in the case of extensive immunohistochemical negativity a defi nitive diagnosis may not be reached. In order to provide clarity, further IHC studies should be performed in the presence of a defi nitive diagnosis based on ultrastructural investigation [29].…”
Section: Discussionmentioning
confidence: 99%
“…1 Immunohistochemical and ultrastructural studies of PNSTs and cPWTs have respectively confirmed the perineural and perivascular origin of tumors indentified by the aforementioned growth models and have allowed their specific subtyping. 1,10,26,30 Hence, cPWTs have been subclassified into hemangiopericytomas, myopericytomas, angioleiomyomas/ sarcomas, angiofibromas, and adventitial tumors, 1 while PNSTs have been subtyped into schwannomas and neurofibromas. 10,15,30 Of the latter, several histological variants have been described.…”
Section: Discussionmentioning
confidence: 99%
“…If the pseudocapsule is breached during surgery or incomplete excision is noted, extensive local regrowth and metastasis can be seen (Shimura et al, 2001). Proper diagnosis of hemangiopericytomas can be challenging from a histopathologic standpoint and recent investigations show that many previous cases diagnosed as such may actually represent one of a spectrum of perivascular wall tumors (Avallone et al, 2007;Palmieri et al, 2013). The originally described microscopic pattern of a hemangiopericytoma consisted of concentric layers of spindle cells arranged http://www.openveterinaryjournal.com J.D.…”
Section: Introductionmentioning
confidence: 99%